High temperature impedance spectroscopy study of non-stoichiometric bismuth zinc niobate pyrochlore. - Tan, Kar Ban; Khaw, C. C.; Lee, C. K.; Zainal, Z.; Tan, Y. P.; Shaari, Hasnizam (Springer Publishing Company, 2009)
Single phase non-stoichiometric bismuth zinc niobate, Bi3Zn1.84Nb3O13.84, was fabricated by a conventional solid state method. The sample was refined and fully indexed on the cubic system, space group Fd3m (No. 227), Z = 4 with a = 10.5579(4) ï¿½. Electrical characterisation was performed using an ac impedance analyser over the temperature range of 25-850 ï¿½C and frequency range of 5 Hz-13 MHz. Typical dielectric response is observed in Bi3 Zn1.84Nb3O13.84 with a high relative permittivity, low dielectric loss and a negative temperature coefficient of capacitance, with the values of 147, 0.002 and -396 ppm/ï¿½C, at 100 kHz at ambient temperature, respectively. This material is highly resistive, with a conductivity of 1ï¿½10-21 O-1ï¿½cm-1 and a high activation energy of ca. 1.59 eV.